Pengaruh Covid-19 Terhadap Praktik Keagamaan di Kecamatan Pomalaa Kabupaten Kolaka - Krisma Lolongan; Hartini Hartini; Hidayah Rahman (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This study aims to determine the influence of COVID-19 on the religious practices of Christians during the pandemic in Pomalaa District, Kolaka Regency. In this study using the theory of change William A. Haviland (1985) in the translation of Haryono Soekanto by using ethnography. The results of the study show that the existence of COVID-19 has a huge influence on people's lives, especially in Pomalaa District, Kolaka Regency. Specifically in religious practices. The influence of COVID-19 has made restrictions on churches and even spiritual activities that are usually carried out are temporarily eliminated such as household worship. Not only that, worship is also carried out online. During the pandemic, activities in the church are very limited and congregants are required to wear masks, wash their hands, sit at a distance and before entering the church, congregants must first check their body temperature to avoid transmission of COVID-19. If anyone is not feeling well, they are advised to return and worship from their homes.